Metabolite Bioactive Contents of Parkia timoriana (DC) Merr Seed Extracts in Different Solvent Polarities - Venty Suryanti; Atmira Sariwati; Fita Sari; Desi Suci Handayani; Hamdan Dwi Risqi (HAYATI Journal of Biosciences, 2022)
Parkia roxburghii G.Don seeds have popular folkloric ethnomedicinal use in the treatment of many diseases especially in Indonesia. Methanol, distilled water, n-hexane, and ethyl acetate extracts from the seeds of Parkia roxburghii were assayed for secondary metabolism quantitative, antioxidant, antidiabetic and antibacterial and activities as well as determined the presence of phytochemical constituents. The extracts were investigated for antioxidant possession by DPPH free-radical (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2’ Azinobis (3-ethylbenz-thiazoline-6-sulfonic-acid) scavenging ability, Antidiabetic potential was invitro assayed by α-amylase inhibition and α-glucosyde inhibition while antibacterially by applying the disk diffusion procedure, as well as refined for the attendance of bioavailable phytochemical components. The result showed the existence of phytochemical components in diverse extracts could attribution free scavenging, antidiabetic and antimicrobial activities. The qualitative results all extracts of Parkia roxburghii seeds have expressed the presence of alkaloid, flavonoid, steroid, terpenoids, saponins and tannin whereas, methanol, distilled water, and n-hexane extracts expressed the presence of anthraquinones, The entire phenolic contents were examined as attested by the Follin-Ciocalteu methods, which varied from 43.82 - 137.42 mg GAE/g. The entire flavonoid compounds were measured with aluminum chloride colorimetric procedure, which varied from 20.42 – 45.90 mg QEDW/g. The total phenolic compound were measure Follin Ciocalteu which varied from 43.82-137.42 mg/g. The alkaloid, saponin, tanic acid, terpenoid and cardiac glycoside quantitative were measured with spectrofotometri UV-VIS which varied from 16.34 – 48.90 mg for alkaloid. The Saponin content varied 1.76 – 16.04 mg/g. Tanic acid which varied 0.21 – 7.29 mg/g. Terpenoid which varied 50.12 – 91.02 mg/g. Cardiac glycoside which varied 7.24-36.53 mg/g. The potential antioxidant were measured with ABTS and DPPH method, the methanol extract is the potential antioxidant. Antidiabetic potential were measured with alfa amylase and alfa glucosyde inhibition, the best antidiabetic is methanol extract. The potential antibacterial and antifungal was the methanol extract for Eschericia Coli and Candida Albicans. The conclusion established the tremendous perspective of the Parkia roxburghii seeds as another option fountain of food supplement, as well as drug components.